The influence of sleep deprivation and obesity on DNA damage in female Zucker rats (Clinics, 2013)
OBJECTIVE: The aim of this study was to evaluate overall genetic damage induced by total sleep deprivation in obese, female Zucker rats of differing ages. METHOD: Lean and obese Zucker rats at 3, 6, and 15 months old were randomly distributed into two groups for each age group: home-cage control and sleep-deprived (N = 5/group). The sleep-deprived groups were deprived sleep by gentle handling for 6 hours, whereas the home-cage control group was allowed to remain undisturbed in their home-cage. At the end of the sleep deprivation period, or after an equivalent amount of time for the home-cage control groups, the rats were brought to an adjacent room and decapitated. The blood, brain, and liver tissue were collected and stored individually to evaluate DNA damage. RESULTS: Significant genetic damage was observed only in 15-month-old rats. Genetic damage was present in the liver cells from sleep-deprived obese rats compared with lean rats in the same condition. Sleep deprivation was associated with genetic damage in brain cells regardless of obesity status. DNA damage was observed in the peripheral blood cells regardless of sleep condition or obesity status. CONCLUSION: Taken together, these results suggest that obesity was associated with genetic damage in liver cells, whereas sleep deprivation was associated with DNA damage in brain cells. These results also indicate that there is no synergistic effect of these noxious conditions on the overall level of genetic damage. In addition, the level of DNA damage was significantly higher in 15-month-old rats compared to younger rats.